2001
DOI: 10.1007/s004540010076
|View full text |Cite
|
Sign up to set email alerts
|

Curvature and Geometry of Tessellating Plane Graphs

Abstract: We show that the growth of plane tessellations and their edge graphs may be controlled from below by upper bounds for the combinatorial curvature. Under the assumption that every geodesic path may be extended to infinity we provide explicit estimates of the growth rate and isoperimetric constant of distance balls in negatively curved tessellations. We show that the assumption about geodesics holds for all tessellations with at least p faces meeting in each vertex and at least q edges bounding each face, where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
180
0
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(184 citation statements)
references
References 15 publications
2
180
0
2
Order By: Relevance
“…Now we present the conditions which have to be satisfied that a planar graph is locally tessellating: Note that these properties force the graph G to be connected. Examples are tessellations R 2 introduced in [BP1,BP2], trees in R 2 , and particular finite tessellations on the sphere mapped to R 2 via stereographic projection.…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…Now we present the conditions which have to be satisfied that a planar graph is locally tessellating: Note that these properties force the graph G to be connected. Examples are tessellations R 2 introduced in [BP1,BP2], trees in R 2 , and particular finite tessellations on the sphere mapped to R 2 via stereographic projection.…”
Section: Proof Of Theoremmentioning
confidence: 99%
“…for example [4,23,24]. From the Gauss-Bonnet formula it follows that a plane graph of non-positive curvature has at least 3 corners.…”
Section: Preliminariesmentioning
confidence: 99%
“…A plane graph G has non-positive curvature if κ(v) 0 for every inner vertex v of G. It can be easily shown that the plane graphs of each of the types (4,4), (3,6), and (6, 3) have non-positive curvature, and from this perspective they have been investigated in a number of papers; cf. for example [4,23,24].…”
Section: Preliminariesmentioning
confidence: 99%
See 2 more Smart Citations